Horizontal coherence in EU social media diplomacy: case of Ukraine - Iarovyi, Dmytro (Information & Media, 2015)
In the discussion of the EU as an international actor, one of the important aspects is foreign policy coherence. One of the instruments of foreign policy is public diplomacy which in the network society is often embodied in the form of digital diplomacy – use of information technologies for achieving diplomatic goals through reaching the networks of information consumers in the Internet.The significance of digital diplomacy for the EU was outlined by numerous politicians and researchers and has actualized after the events in Ukraine when the refusal of the government to sign the Association Agreement led to the wave of escalating protests, overthrow of the President, a deep political crisis and territorial losses (annexation of the Crimea by Russia). The EU digital diplomacy has been actively embodied in this process, but sometimes it appeared to be not an example of a concerted action.The aim of this article is to verify the horizontal coherence of the EU social media diplomacy in the case of the EU–Ukraine relations. The results allow us to conclude that, despite some minor failures (some unsuited rhetoric, lack of references to each other and of interactivity), on the horizontal level the EU is mostly coherent in maintaining its digital diplomacy, which allows to speak about its succeeding in self-presentation as an international actor in the Internet communication.
Keywords: EU foreign policy; coherence; digital diplomacy; social media; public diplomacy; soft power